Congruence and Conflict in the Higher-Level Phylogenetics of Squamate Reptiles: An Expanded Phylogenomic Perspective. (28th August 2020) - Singhal, Sonal; Colston, Timothy J; Grundler, Maggie R; Smith, Stephen A; Costa, Gabriel C; Colli, Guarino R; Moritz, Craig; Pyron, R Alexander; Rabosky, Daniel L
Abstract: Genome-scale data have the potential to clarify phylogenetic relationships across the tree of life but have also revealed extensive gene tree conflict. This seeming paradox, whereby larger data sets both increase statistical confidence and uncover significant discordance, suggests that understanding sources of conflict is important for accurate reconstruction of evolutionary history. We explore this paradox in squamate reptiles, the vertebrate clade comprising lizards, snakes, and amphisbaenians. We collected an average of 5103 loci for 91 species of squamates that span higher-level diversity within the clade, which we augmented with publicly available sequences for an additional 17 taxa. Using a locus-by-locus approach, we evaluated support for alternative topologies at 17 contentious nodes in the phylogeny. We identified shared properties of conflicting loci, finding that rate and compositional heterogeneity drives discordance between gene trees and species tree and that conflicting loci rarely overlap across contentious nodes. Finally, by comparing our tests of nodal conflict to previous phylogenomic studies, we confidently resolve 9 of the 17 problematic nodes. We suggest this locus-by-locus and node-by-node approach can build consensus on which topological resolutions remain uncertain in phylogenomic studies of other contentious groups. [Anchored hybrid enrichment (AHE); gene tree conflict; molecular evolution; phylogenomic concordance; target capture; ultraconserved elements (UCE).]